Identification of key amino acid residues in AtUMAMIT29 for transport of glucosinolates - Meyer, Lasse; Crocoll, Christoph; Halkier, Barbara Ann; Mirza, Osman Asghar; Xu, Deyang (Frontiers in Plant Science, 2023)
Glucosinolates are key defense compounds of plants in Brassicales order and their accumulation in seeds is essential for protection of the next generation. Recently, members of Usually Multiple Amino acids Move In and out Transporter (UMAMIT) family were shown to be essential for facilitating transport of seed-bound glucosinolates from site of synthesis within the reproductive organ to seeds. Here, we set out to identify amino acid residues responsible for glucosinolate transport activity of the main seed glucosinolate exporter UMAMIT29 in Arabidopsis thaliana. Based on a predicted model of UMAMIT29 we find that the binding cavity consists of 51 residues, of which four are highly conserved residues across all the analysed homologs of UMAMIT29. A comparison of the putative substrate binding site of homologs within the brassicaceous-specific, glucosinolate-transporting clade with the non-brassicaceous-specific, non-glucosinolate-transporting UMAMIT32 clade identified 11 differentially conserved sites. When each of the 11 residues of UMAMIT29 was individually mutated into the corresponding residue in UMAMIT32, five mutant variants (UMAMIT29#V27F, -M86V, -L109V, -Q263S and -T267Y) reduced glucosinolate transport activity by ⁓75-97% compared to wildtype UMAMIT29. This suggests that these residues are key for UMAMIT29-mediated glucosinolate transport activity and thus potential targets for blocking the transport of glucosinolates to the seeds.